2007
DOI: 10.1016/j.jmb.2006.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Action of Transcription Factors in the Control of Transferrin Receptor Expression in Human Brain Endothelium

Abstract: SummaryBrain endothelium has a distinctive phenotype, including high expression of transferrin receptor, pglycoprotein, claudin-5 and occludin. Dermal endothelium expresses lower levels of the transferrin receptor and it is absent from lung endothelium. All three endothelia were screened for transcription factors that bind the transferrin receptor promoter and show different patterns of binding between the endothelia. The transcription factor YY1 has distinct DNA-binding activities in brain endothelium and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Previously we have found that both Sp1 and Sp3 can be detected in hCMEC/D3 by EMSA-supershift assay with a consensus Sp oligonucleotide probe. Moreover, the activity of Sp3 is higher in brain endothelium, than non-brain endothelium [9]. The different techniques, all indicate that Sp3 is strongly expressed in brain endothelium, although Sp1 is also present.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously we have found that both Sp1 and Sp3 can be detected in hCMEC/D3 by EMSA-supershift assay with a consensus Sp oligonucleotide probe. Moreover, the activity of Sp3 is higher in brain endothelium, than non-brain endothelium [9]. The different techniques, all indicate that Sp3 is strongly expressed in brain endothelium, although Sp1 is also present.…”
Section: Resultsmentioning
confidence: 90%
“…Brain endothelium expresses particularly high levels of Sp3 in comparison with lung and dermal endothelium [9]. Sp1 is the prototype of a large family of transcription factors which bind GC-rich segments [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of the 24-hour rhythm in the expression of TfR1 gene by c-MYC Among these, c-MYC is a potent activator of TfR1 gene transcription in mice and humans, and the transactivation effect was elicited through binding to the CACGTG E-box located in the first intron region (18,19). In addition, CLOCK/ BMAL1 heterodimers also bind cooperatively to CACGTG E-box sequences and regulate the rhythmic expression of their target genes (2).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 In addition to the indirect regulation that YY1 has for claudin expression through YY1’s up-regulation of Snail, 20,21 a direct relationship between YY1 and claudin expression has been reported by Holloway et al 58 These investigators demonstrated that the promoter regions of claudin-5 retain specific target sites for the Sp-family transcription factors TFIID and YY1, suggesting that YY1 could regulate claudin expression directly. The 5′ promoter of claudin-5 was also found to contain GC-rich segments with common sequence motifs, suggesting that this gene is regularly acted upon by common transcriptional factors such as YY1.…”
Section: Putative Direct Regulation Of Emt Gene Products By Yy1: mentioning
confidence: 94%